The semantic sphere 1 : computation, cognition, and information economy - Levy, Pierre, 1956- (London : ISTE, 2011)
'The new digital media offers us an unprecedented memory capacity, an ubiquitous communication channel and a growing computing power. How can we exploit this medium to augment our personal and social cognitive processes at the service of human development? Combining a deep knowledge of humanities and social sciences as well as a real familiarity with computer science issues, this book explains the collaborative construction of a global hypercortex coordinated by a computable metalanguage. By recognizing fully the symbolic and social nature of human cognition, we could transform our current opaque global brain into a reflexive collective intelligence'--
Includes bibliographical references and index.
Keywords: Semantic Web; Information society; Human information processing; Metalanguage